A estratégia chinesa frente a Indústria 4.0, uma análise comparativa. - Lucena, Felipe Andrade Santos (2019)
This study is about the phenomenon of the 4th industrial revolution and the top tier countries roles in this revolution. Actually, there is a retaken of industrial policies by the main manufacture countries. That phenomenon is associated to the new wave of Information Technologies which affect the whole economic system, this change is called by researches as the 4th industrial revolution. The 4th industrial revolution brought the necessity to rethink industrial policy by the main global players on the manufacture market. Germany is one of those players and pioneer in studying the 4th industrial revolution, Germany also counts on several private institutes that act as drivers of industrial policy. The United States of America in other hand have an industrial strategy for the fourth industrial revolution with focus to resume and recover part of its industrial structure lost in recent days to peripheral countries. In other hand, Japan and South Korea are modernizing and maintaining the industry of their most prominent sectors. Finally, China, together with the major powers, prepared a series of measures to prepare for the fourth industrial revolution, in the same context as they were planned for the elaboration of an industrial week. to become one of the leading manufacturing companies of the year 2050.